Kinetics of the Release of Nicotinamide Absorbed on Partially Neutralized Poly(acrylic-co-methacrylic acid) Xerogel under the Conditions of Simultaneous Microwave Heating and Cooling - Jelena D. Jovanovic; Borivoj K. Adnadjevic (Gels, 2021)
The kinetics of release of nicotinamide (NIAM) that was absorbed on partially neutralized poly(acrylic-co-methacrylic) (PAM) xerogel/hydrogel, under the conditions of simultaneous microwave heating and cooling (SMHC) were examined. The kinetics curves of NIAM release into an aqueous solution at temperatures of 308–323 K were recorded. By applying the model-fitting method (MFM), it was found that the kinetics of NIAM release can be modeled by a kinetic model of a first-order chemical reaction. The values of the release rate constants (kM) at different temperatures were calculated, and their values were found to be within the range 8.4 10−3 s −1−15.7 10−3 s−1. It has been established that the Arrhenius equation was valid even in the conditions of SMHC. The values of the kinetic parameters (activation energy (Ea) and pre-exponential factor (A) of the NIAM release process adsorbed on PAM xerogel/hydrogel were calculated as follows: Ea = 25.6 kJ/mol and ln (A/s−1) = 5.21. It has been proven that the higher value of the rate constant at SMHC in relation to CH is not a consequence of the overheating of the reaction system or the appearance of “hot-points”. The values of change of the enthalpy of activation (ΔH*) and the change of entropy of activation (ΔS*) were calculated as follows: ΔH* = +23.82 kJ/mol and ΔS* = −201.4 J/mol K. The calculated higher values of the kinetic parameters and thermodynamic parameters of activation are explained by the formation of a specific activated complex under SMHC, whose structure and degree of order are different than in the one formed under CH.